Import competition from China in manufacturing after the financial crisis: Evidence for European regions - Werner Hölzl (Austrian Institute of Economic Research (WIFO), 2021)
This research studies the effect of import competition from China for the period after the financial crisis 2008-09 until 2014. It draws on a unique dataset containing employment information for 248 regions in the EU. The uncovered coefficients are statistically not significant, indicating that Chinese imports were not an important driver of deindustrialisation in Europe in the period analysed. The estimates are imprecise, however. An analysis of the economic importance of the results leads to the conclusion that Chinese import competition was not a primary driving force of European manufacturing employment. Possible explanations for the lack of significant results are discussed.
Keywords: F16; J13; R11; 330; Trade; Employment; China; EU; Regions